Point-Of-Care Capillary Refill Technology Improves Accuracy of Peripheral Perfusion Assessment - Sheridan, David C.; Cloutier, Robert L.; Samatham, Ravi; Hansen, Matthew L. (Frontiers in Medicine, 2021)
Background Peripheral perfusion assessment is used routinely at the bedside by measuring capillary refill time (CRT). Recent clinical trials have shown evidence to its ability to recognize conditions with decreased end organ perfusion as well as guiding therapeutic interventions in sepsis. However, the current standard of physician assessment at the bedside has shown large variability. New technology can improve the precision and repeatability of CRT affecting translation of previous high impact research. Methods This was a prospective, observational study in the intensive care unit and emergency department at a quaternary care hospital using a noninvasive finger sensor for CRT. The device CRT was compared to the gold standard of trained research personnel assessment of CRT as well as to providers clinically caring for the patient. Results Pearson correlations coefficients were performed across 89 pairs of measurements. The Pearson correlation for the device CRT compared to research personnel CRT was 0.693. The Pearson correlation for the provider CRT compared to research personnel CRT was 0.359. Conclusions New point-of-care technology shows great promise in the ability to improve peripheral perfusion assessment done at the bedside in the emergency department triage and resuscitation. This standardized approach allow for better translation of prior research that is limited by the subjectivity of manual visual assessment of CRT.